The drugs based on molecular structures of antimicrobial peptides and their therapeutic potential in the treatment of infectious diseases of the respiratory tract (part 1) - А.Е. Abaturov; Т.А. Kryuchko; G.O. Lezhenko (Zaslavsky O.Yu., 2017)
The actual trend of recent researches focused on finding and developing new antimicrobial drugs is a study of molecular structures of endolysins, bacteriocins, antimicrobial peptides, and also the creation of preparations with monoclonal antibodies targeted to bacterial virulence factors, probiotics and vaccines. The antimicrobial peptides interacting with bacteria lead to the destruction of the bacterial wall due to a violation of its integrity, namely the formation of cylindrical, toroidal pores or by rupturing the internal membrane of the bacterial wall. The majority of human antimicrobial peptides are represented by cathelicidin and defensins. Currently, active scientific researches are under way to create derivatives or analogues of human defensins, which could be used as medicines in the treatment of infectious diseases of the respiratory tract.